2003
DOI: 10.1007/s00383-002-0771-x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic aspects of cervical lymphadenopathy in children in the developing world: a study of 1,877 surgical specimens

Abstract: Chronic cervical lymphadenopathy is a common clinical problem frequently requiring surgical biopsy. To evaluate the characteristics of surgically excised cervical lymph nodes (LN) in children in a developing country, we studied 1,332 children less than 15 years old (1,877 surgically removed cervical LNs) over a 23-year period (1976-1999). Indications for biopsy included failure to respond to antibiotic therapy, rapid increase in size, hard, matted LNs in the preauricular, supraclavicular, and posterior triangl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
57
1
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(71 citation statements)
references
References 17 publications
10
57
1
3
Order By: Relevance
“…This may be due to reactive hyperplasia in lymph nodes draining the site of malignant lesion, which do not shows metastatic deposit due to early diagnosis and surgical excision. This was consistent with study of Moore SW et al found 47.8% 0f reactive lesions [3].…”
Section: Discussionsupporting
confidence: 92%
“…This may be due to reactive hyperplasia in lymph nodes draining the site of malignant lesion, which do not shows metastatic deposit due to early diagnosis and surgical excision. This was consistent with study of Moore SW et al found 47.8% 0f reactive lesions [3].…”
Section: Discussionsupporting
confidence: 92%
“…Though fine needle aspi ration cytology is commonly used to establish the etiological diagnosis, excision biopsy and histopathology of the lymph node remains the "gold standard" for diagnosis 2,3,4 of lymphadenopathy. In our study males were more commonly affected than females.…”
Section: Discussionmentioning
confidence: 99%
“…These changes may be particularly marked in younger individuals, but may be observed in all ages. [1][2][3] The most important consideration in assessing a reactive lymph node is in its distinction from a neoplasm, mainly the various types of malignant lymphoma. In a minority of circumstances, the specific pattern of reaction may strongly suggest a specific etiology.…”
mentioning
confidence: 99%